Oral hygiene, dietary habits and prevalence of dental caries in adolescents from rural and urban areas in Rio Grande do Sul, Brazil - BORGES,Tássia Silvana (2017)
ABSTRACT Objective: To determine the condition of oral hygiene, dietary habits and prevalence of dental caries in adolescents, listing these habits and comparing residents from rural and urban areas. Methods: Cross-sectional study involving of 623 adolescents of both sexes, aged 12 to 17 year old in Santa Cruz do Sul, Brazil. Data were collected through sociodemographic questionnaires and dental examination. We conducted a descriptive analysis of the exposure variables and outcome. A bivariate analysis was then performed using the Chi-square test. Results: The prevalence of caries was 63.6%, in which adolescents living in rural areas had a prevalence of 70.7% and 56.4% in the urban area. The level of mother’s education ≤4 years and socioeconomic class B1/B2 and C1/C2 showed statistically significant differences between the areas of residence. Among the demographic variables, the rural area showed a higher prevalence of caries. Conclusion: The results showed a high prevalence of dental caries among the adolescents studied and indicate a correlation between prevalence and the low level of mother’s education, socioeconomic status (low to medium) and residence in rural areas. It should be understood that, while the multifactorial nature and stratified caries actions are not taken into consideration, the actions implemented will continue to fail, frustrating the expectations set by government entities.